Development of nutrient-rich growing media with hazelnut husk and municipal sewage sludge. Issue 17 (2nd September 2018) - Dede, Omer Hulusi; Ozdemir, Saim
ABSTRACT: The aim of the present study was to develop structurally stable, nutrient-rich and environmentally safe growing media by combining waste material: crop residue hazelnut husk (HH) and municipal sewage sludge. In order to achieve this goal, lignocellulosic HH residue was mixed with nutrient-rich sewage sludge (S) in various proportions: HH 100%; HH + S1 87.5% : 12.5%; HH + S2 75% : 2 5%; HH + S3 50% : 5 0%. Following composting, the key physical, chemical and microbiological properties of the growing media were characterized for long-term ornamental nursery crops. The addition of S to the mixture had both significant detrimental and remedial effects on physical properties such as reduced total porosity and water-holding capacity, whilst improved the air capacity, wettability and shrinkage. S content of growing media significantly enriched the plant nutrients, especially the most desired soluble and organic nitrogen fractions and micro nutrients. Germination tests and microbiological analysis confirmed the products as environmentally safe ornamental growing media. We conclude that composting of HH with S is a viable alternative for the development of nutrient-rich growing media and recycling of such waste in the ornamental industry could be a beneficial method in order to sustain waste management and crop production.